2012
DOI: 10.4204/eptcs.95.11
|View full text |Cite
|
Sign up to set email alerts
|

Graphical Classification of Entangled Qutrits

Abstract: A multipartite quantum state is entangled if it is not separable. Quantum entanglement plays a fundamental role in many applications of quantum information theory, such as quantum teleportation. Stochastic local quantum operations and classical communication (SLOCC) cannot essentially change quantum entanglement without destroying it. Therefore, entanglement can be classified by dividing quantum states into equivalence classes, where two states are equivalent if each can be converted into the other by SLOCC. P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In [CK10], Coecke and Kissinger observed that there exists, in fact, a commutative Frobenius algebra (c , d , m , u ) on the qubit, whose spider with three outputs and no inputs is proportional to the | W state. This is defined by This was partially extended to the case of qutrits, that is, 3-dimensional Hilbert spaces, where an intermediate class between special and anti-special appears, in [Hon12].…”
Section: The Entanglement Classification Problemmentioning
confidence: 99%
“…In [CK10], Coecke and Kissinger observed that there exists, in fact, a commutative Frobenius algebra (c , d , m , u ) on the qubit, whose spider with three outputs and no inputs is proportional to the | W state. This is defined by This was partially extended to the case of qutrits, that is, 3-dimensional Hilbert spaces, where an intermediate class between special and anti-special appears, in [Hon12].…”
Section: The Entanglement Classification Problemmentioning
confidence: 99%
“…For dimensions 3 and above, only some of these algebras extend to Frobenius algebras, and it becomes a straightforward task to enumerate those that are. The classification of Frobenius states for dimension 3 was completed this year by Honda [32]. As in the case for two dimensions, a…”
Section: Classifying Frobenius Statesmentioning
confidence: 99%